The Needs For Capacity Building In Local Government In Malaysia (With Regards To Property Taxation Administration) - Daud, Dzurllkanian @ Zulkarnain; Alias, Buang; Muthuveerappan, Chitrakala (2008)
Property tax is a widely used fiscal tool because it is a vital source of income for urban authorities in developing countries like Malaysia. The tax, levied on land and buildings and is based on either improved or annual value. Valuation of these properties is a tedious and continuous process. In Malaysia, the revaluation exercise is still carried out manually. Due to financial, labour, and time constraints, most Local Governments in Malaysia are unable to meet this requirement and only capable to carry out revaluation every 10 years or more. Property taxation administration involves and requires good and skilled administrators, efficient system (property tax administration system) and advanced or efficient technology. University Teknologi Malaysia (UTM) has embarked on research and development of Computer Assisted Mass Appraisal (CAMA) for rating valuation to assist Department of Property Valuation in Local Governments to improve their capacity with regards to property taxation administration for the purpose of complying with the requirements of the Local Government Act 1976 which stipulated that every Local Government has to carry out revaluation every five (5) years. This paper discusses the capacity building in local governments in Malaysia and identifies areas in which they are lacking.